Depthwise variation in selected soil properties as influenced by tillage and residue management in sandy loam soil of North-West Himalayas, India - PAL, SHARMISTHA; YADAV, R P; ARYA, S L; K, SATHIYA; BHUTIA, P L (The Indian Journal of Agricultural Sciences, 2022)
The present study aimed to determine the effect of varying tillage and residue management in a sandy loam soil under maize (Zea mays L.)-wheat (Triticum aestivum L.) sequence. The research was carried out at ICAR- Indian Institute of Soil and Water Conservation, Research Centre, Chandigarh, research farm, located at Panchkula, Haryana, in maize (kharif)-wheat (rabi) cropping sequence during 2009–2017. Six treatments implemented were Conventional tillage (CT); Deep tillage once in three years (DT); Conventional tillage with integrated nutrient management (CT-INM); Conventional tillage with brown manuring in maize + cowpea (1:2) and wheat + pea (4:1) ratio (CT-BM); Conservation tillage (CST) ; Conservation tillage with brown manuring (CST-BM). The compaction level attained under conservation tillage based systems were lower than the corresponding levels in the conventional tillage control. The highest percentage of macro aggregates was found in CST-BM treatment (48%), followed by CST (45%) and CT, DT and CT-INM recorded much lesser macro aggregate (29.3, 28 and 31%). Conventional tillage (CT) reduced macroaggregates with a concomitant increase in microaggregates (<0.25 mm) percentage. The mean soil moisture percentage average in surface (0–15 cm) and sub surface soil (15–30 cm) were found to be higher under DT, CST and CST-BM treatments over CT and CT-INM treatments. In general, the soil moisture was found to be proportional to the amount of biomass added under various treatments. The mean soil available nitrogen were 15.4% and 17.5% higher under CT-BM and CST-BM treatments respectively, over the control (CT).